Control of Neuronal Excitability by Cell Surface Receptor Density and Phosphoinositide Metabolism - Martin Kruse; Martin Kruse; Rayne J. Whitten (Frontiers Media S.A., 2021)
Phosphoinositides are members of a family of minor phospholipids that make up about 1% of all lipids in most cell types. Despite their low abundance they have been found to be essential regulators of neuronal activities such as action potential firing, release and re-uptake of neurotransmitters, and interaction of cytoskeletal proteins with the plasma membrane. Activation of several different neurotransmitter receptors can deplete phosphoinositide levels by more than 90% in seconds, thereby profoundly altering neuronal behavior; however, despite the physiological importance of this mechanism we still lack a profound quantitative understanding of the connection between phosphoinositide metabolism and neuronal activity. Here, we present a model that describes phosphoinositide metabolism and phosphoinositide-dependent action potential firing in sympathetic neurons. The model allows for a simulation of activation of muscarinic acetylcholine receptors and its effects on phosphoinositide levels and their regulation of action potential firing in these neurons. In this paper, we describe the characteristics of the model, its calibration to experimental data, and use the model to analyze how alterations of surface density of muscarinic acetylcholine receptors or altered activity levels of a key enzyme of phosphoinositide metabolism influence action potential firing of sympathetic neurons. In conclusion, the model provides a comprehensive framework describing the connection between muscarinic acetylcholine signaling, phosphoinositide metabolism, and action potential firing in sympathetic neurons which can be used to study the role of these signaling systems in health and disease.